Enhancing Students' Reading Comprehension Through Jigsaw at Vocational High School - khoiriyah, khoiriyah (English Education:Journal of English Teaching and Research, 2019)
The objective of this research is to increase students’ reading comprehension through jigsaw and to describe classroom situation when jigsaw is applied in teaching reading. Classroom action research was carried out through observasion, interview, test consisting of two cycles. 35 Multi Media students of tenth grade at SMKN 2 Kediri was assigned as participant. Analyses resulted that jigsaw could enhance the students’ reading comprehension and classroom situation. It can be seen that the students were eager, interested and motivated to participate in reading class. During teaching reading, the students showed more active than before and the class atmosphere seems more alive. Then, students’ reading achievement in cycle two improved than in cycle one. The students’ average score was higher from 71,85 in the first cycle to 79,85 in the second cycle. Keywords: Reading Comprehension, Jigsaw, Vocational High School